Incidence and course of COVID-19 hospitalizations among patients with familial Mediterranean fever. (22nd July 2021) - Kharouf, Fadi; Ishay, Yuval; Kenig, Ariel; Bitan, Menachem; Ben-Chetrit, Eldad
Abstract: Objectives: To evaluate the incidence of hospitalization for coronavirus disease 2019 (COVID-19) in patients with FMF, as compared with the general population, and to compare the disease course between FMF inpatients, and age-, sex-, ethnicity- and comorbidity-matched non-FMF COVID-19 inpatients. Methods: We used electronic medical records to obtain data about the total number of the insured population and the number of FMF patients in the two largest health management organizations in Jerusalem, Clalit and Meuhedet. The total number of COVID-19 inpatients at the Hadassah Medical Center, including those with FMF, for the period between 1 February 2020 and 10March 2021, was retrieved from the electronic medical records of Hadassah. COVID-19 course was compared between the FMF inpatient group and age-, sex-, ethnicity- and comorbidity-matched non-FMF COVID-19 inpatients. Each FMF inpatient was matched with two non-FMF controls. Results: We found no statistically significant difference in the odds of hospitalization for COVID-19 between FMF patients and the non-FMF population (0.46% vs 0.41%, P = 0.73). Furthermore, we found similar disease severity and therapeutic approach in FMF COVID-19 inpatients and matched non-FMF COVID-19 inpatients. Conclusions: Neither FMF nor baseline colchicine therapy, appear to affect the incidence of hospitalization for COVID-19 or the disease course, in terms of severity and therapeutic approach.